Corporate social responsibility report readability, credit ratings and cost of borrowing. Issue 5 (25th October 2022) - Yu, Kun; Garg, Priya
Abstract : Purpose: This study aims to investigate how credit rating agencies and banks, important credit market participants, incorporate corporate social responsibility (CSR)-related information in their assessment of firm's creditworthiness. Design/methodology/approach: The authors collect stand-alone CSR reports published by Fortune 500 companies from 2002 to 2014 and use file size as a readability measure to investigate the impact of stand-alone CSR reports' readability on firms' credit ratings and cost of borrowing. Findings: The authors find that firms with higher CSR report readability enjoy higher credit ratings and lower costs of bank loans, suggesting that rating agencies and banks perceive lower default risk for firms with more readable CSR reports. Further analysis indicates that the positive association between CSR report readability and credit ratings is more pronounced for firms with high CSR performance. Conversely, the negative association between CSR report readability and bank loan spreads is more pronounced for firms with low CSR performance and credit quality, suggesting complementary roles of rating agencies and banks in their use of CSR reports. Originality/value: Overall, the results highlight the importance of improving the textual characteristics of CSR reports, especially readability, in reducing information risk in the credit market.